Alternative Ways of Funding Public Transport: A Case Study Assessment - Ubbels, Barry; Nijkamp, Peter; Verhoef, Erik; Potter, Steve; Enoch, Marcus (European Journal of Transport and Infrastructure Research, 2001)
Public transport traditionally has been, and still is, heavily subsidised by local or national governments, which have been motivated by declining average cost arguments, social considerations, and the desire to offer an alternative to private car use. Conventional sources for funding, including general taxes on labour, in many occasions have become harder to sustain for various reasons. This paper explores alternative, increasingly implemented, sources of funding, i.e., local charges or taxes that are hypothecated to support (urban) public transport (such as local sales taxes, parking charges etc.). Based on an overview of several case-studies all over the world, it is found that there is a large potential for applying unconventional charging mechanisms. Not only as means of raising financial support for public transport systems, but also as a method of sending appropriate (from a sustainable point of view) pricing signals to transport use.